(untitled) (UKLO Proceedings, 2025)
The United Nations (UN) 2030 Agenda and Sustainable Development Goals (SDGs) present global vision for achieving social, economic and environmental balance. However, implementing sustainability is fraught with political dynamics and complex policy challenges. This study examines how the distribution of power between state and non-state actors influences sustainable policymaking at different levels of government. Conflicts of interest often arise among business, civil society and government, which complicates efforts to align common goals. International institutions play an important role in promoting green policies but face unique challenges, particularly in developing countries that must balance economic growth with environmental commitments. This study highlights significant policy limitations and bureaucratic inefficiencies that hinder effective SDG implementation. A shift towards multi-level governance is essential, given the increasing involvement of local and private actors. Ultimately, achieving the 2030 Agenda depends on strengthening cooperation among stakeholders and implementing inclusive policies that are responsive to multiple interests.